Relationship between pancreatic cancer‐associated diabetes and cachexia. Issue 4 (25th February 2020) - Liao, Wei‐Chih; Chen, Peng‐Ruei; Huang, Cheng‐Chieh; Chang, Yen‐Tzu; Huang, Bo‐Shih; Chang, Chin‐Chen; Wu, Ming‐Shiang; Chow, Lu‐Ping
Abstract: Background: Pancreatic cancer‐associated diabetes mellitus (PCDM) is a paraneoplastic phenomenon characterized by worsening hyperglycaemia and weight loss. Galectin‐3 and S100A9, mediators of PCDM, have pro‐inflammatory functions and might thereby induce systemic inflammation and cachexia. We aimed to examine whether PCDM directly mediates cachexia. Methods: Consecutive pancreatic cancer (PC) patients with and without PCDM ( n  = 88 each) with complete information were included. Cachexia was defined as weight loss >5% within 6 months or weight loss >2% and body mass index <20 kg/m 2 or sarcopenia. Skeletal muscle mass was measured with lumbar skeletal muscle index (SMI) using computed tomography images. Cachexia‐related parameters (prevalence of cachexia, weight loss, and SMI) were compared between patients with and without PCDM. Relations between cachexia‐related parameters and fasting blood glucose or serum levels of galectin‐3 and S100A9 were analysed by Spearman correlation and logistic regression analyses. Results: One hundred two (58.0%) patients had cachexia at diagnosis. No significant differences existed between patients with and without PCDM in prevalence of cachexia (64.8% vs. 51.1%, P  = 0.093), percentage of weight loss (median 6.8 vs. 4.0, P  = 0.085), and SMI (median 45.8 vs. 45.3 cm 2 /m 2 in men, P  = 0.119; 34.9 vs. 36.3 cm 2 /m 2 in women, P  = 0.418). In patients with cachexia, the percentage of weight loss and SMI were also similar between patients with and without PCDM. In patients with PCDM, fasting blood glucose was comparable between patients with and without cachexia ( P  = 0.458) and did not correlate with the percentage of weight loss ( P  = 0.085) or SMI ( P  = 0.797 in men and 0.679 in women). Serum S100A9 level correlated with fasting blood glucose (correlation coefficient 0.213, P  = 0.047) but not with the percentage of weight loss ( P  = 0.977) or SMI ( P  = 0.247 in men and 0.458 in women). Serum galectin‐3 level also did not correlate with the percentage of weight loss ( P  = 0.226) and SMI ( P  = 0.201 in men and 0.826 in women). Primary tumour size was associated with cachexia (adjusted odds ratio per 1 cm increase 1.28, 95% confidence interval 1.02–1.60, P  = 0.034), whereas PCDM, fasting blood glucose, and levels of galectin‐3 and S100A9 were not predictors of cachexia. Conclusions: Neither fasting blood glucose nor levels of galectin‐3 and S100A9 were associated with cachexia‐related parameters. Mediators of PCDM and hyperglycaemia do not directly mediate PC‐induced cachexia.